Rights of nature and the indigenous Peoples in Bolivia and Ecuador: a Straitjacket for Progressive development Politics? - Rickard LALANDER (Revista Iberoamericana de Estudios de Desarrollo)
Is it possible to justify resource extractivism to provide progressive welfare politics and still respect the constitutional rights of nature? The Indigenous concept of Sumak Kawsay on human beings living in harmony with each other and the environment is the fundamental framing of the new constitutions of Ecuador and Bolivia. These constitutional reforms embrace strengthened proper rights of nature and similarly of ethnic rights. However, the same constitutions grant the State the right to exploit and commercialize natural resources and extractivism has increased. This study revises the tensions between welfare politics, extractivism and the rights of nature and the Indigenous peoples in the new constitutional settings of Bolivia and, particularly, Ecuador. The article argues that Sumak Kawsay challenges dominating understandings of the concepts of welfare, common good and development, and likewise that a pragmatic approach is applied by national governments towards the constitutional rights of nature amidst other human values.